ENCODING THE INFORMATION IN A LOGISTICAL SYSTEM: ENCODING THE INFORMATION IN A LOGISTICAL SYSTEM - Kodjeykov, Rumen; Djankov, Plamen; Encheva, Emiliq (JOURNAL SCIENTIFIC AND APPLIED RESEARCH, 2023)
Codification of information and its protection is a priority in the management of logistics systems. The structure of the Codification number reported revenues and expenditures of special purpose products for a certain period of time. The use of this approach in a number of member states of the European Union. Study aims to develop an identification system for logistics standardization document information reporting of special purpose products , and to provide a database for production, storage and consumption quantities stored in logistics bases . Investigates inter-branch relations relevant for decisions about incoming and outgoing material flows . Adoption of standard solutions for coding the database reflects not only on the technical level of production, but also on the consumption and exploitation.